COMMON ERRORS IN STUDENTS’ SPELLING ON THE REQUIRED WORDS FOR THE SEVENTH GRADERS - Ida Rukmana Sari (Universitas Pesantren Tinggi Darul Ulum Jombang, 2015)
The beginner level students often make mistakes and errors in producing L2 (second language). The errors in students’ writing may occur in paragraphs, punctuations, articles, spellings, and conjunctions. Therefore it is not rare when L2 learners write words freely as they heard, for example, a student might write “Spel it rait” for “Spell it right” or “Shi is my techer” for “She is my teacher”. Based on such phenomenon, this study investigated the spelling errors commonly made by the students in writing the required words for the 7th grade. The design of this study was descriptive qualitative. The analysis was based on the errors analysis theory. The data were the students writing on the required words and the result of interview with the students. The respondents of this study were eight students that were categorized as novice low students. The data were analyzed to know the types of errors that the students commonly made and the factors that underlay the errors. The result of this study showed that the errors related to the interference of Bahasa Indonesia into English. Spelling errors for all respondents were highly concentrated in unrecognizable and substitution. Students’ spelling errors in unrecognizable were 141, substitutions 79, omission 50, addition 24 and segmentation 11 words. The factors contributing to the errors were markedness and language distance. The errors made by the students regarding to interference are most contributing the errors as well because some elements in L2 (English) are pertained more marked compared to those in L1 (Bahasa Indonesian). The linguistic difference between L1 and L2 also brings difficulties in the acquisition of L2. The language system in both language families is fundamentally different. The important results of this research is that the difference between L1 and L2 spelling systems result in errors of spelling in the L2. An understanding of the structure of L1 spelling and the mistakes made in the spelling of the word of L2, as well as an understanding of the level of knowledge the learners have about the structure of L1 and L2 spelling systems, will help the course of teaching and learning. In consequence, giving more practice and drilling on the required words that were frequently written incorrectly will be very useful in teaching process. Keywords: L1 interference, Markedness, Novice low